MFU-4 - A metal-organic framework for highly effective H2/D 2 separation - Teufel, Julia; Oh, Hyunchul; Hirscher, Michael; Wahiduzzaman, Mohammad; Zhechkov, Lyuben; Kuc, Agnieszka; Heine, Thomas; Denysenko, Dmytro; Volkmer, Dirk (Advanced Materials, 2013)
The metal-organic framework, MFU-4, possessing small cavities and apertures, is exploited for quantum sieving of hydrogen isotopes. Quantum mechanically, a molecule confined in a small cavity shows an increase in effective size depending on the particle mass, which leads to a faster deuterium adsorption from a H2/D2 isotope mixture. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: gas adsorption; hydrogen isotopes; isotope separation; metal-organic frameworks; quantum sieving